Variation of morphology, anatomy and nutrition contents of local cultivar mentik rice based on the altitudes at Ngawi District, East Java, Indonesia - SURANTO SURANTO; A.T. SYAHIDAH; EDWI MAHADJOENO (Biodiversitas Journal of Biological Diversity, 2018)
Suranto, Syahidah AT, Mahadjoeno E. 2018. Variation of morphology, anatomy and nutrition contents of local cultivar mentik rice based on the altitudes at Ngawi District, East Java, Indonesia. Biodiversitas 19: 652-659. The purposes of this research were to examine the variation in morphology, anatomy and nutrition contents of rice plants grown at three different altitudes at Ngawi District, East Java, Indonesia. The plant samples were collected from three different altitudes (200, 500 and 900 m asl. respectively). The morphological characters of leaf, root and stem were used in this examination, while Paraffin method was employed to look at the anatomical appearances. To look at the content of lipids and proteins, Soxhlet and Kjeldahl methods were used, while the Iodocolorymetre method was chosen to test the amylose content. Randomized Complete Block Design (RCBD) with one factor, namely altitude was used in this research. Morphological and anatomical characters and nutrition contents of rice plant were analyzed using one way of ANOVA. The results showed that the length and diameter of roots, plant height and also stem diameter were declining due to a higher altitude. On the other hand, the length of leaf, the number of roots, the total number of stomata and also the ratio of length per diameter of stomata increased, and so did the number of aerenchyma space roots and stems. In general, there was a tendency of decreasing amylose and protein contents due to higher altitudes.